Awareness and Perception of Office Property Users on Green Building in Lagos, Nigeria (International Journal of Built Environment and Sustainability, 2018)
This study examined the level of awareness, medium of awareness and the perceptions of office property users on Green building and their features in Lagos, Nigeria. The study sampled 352 office property users of 176 properties in the property portfolio of Estate Surveyors and Valuers in Lagos. Data was collected with the use of questionnaire administration. Using frequency counts and measures of relative perception index, the study revealed that majority of the users were not aware of green building. Only 23.6% were aware, and the predominant medium of awareness among these few was the Television. It was also revealed in the result that most of the users perceive green building as more of an environmental concept costing more to build and operate. The study concluded that there is need for more sensitisation on green building. Also, a balance information spread, especially on the social and economic benefits of green building is important for successful implementation of green building in the study area.
Keywords: Awareness; Green Building; Office property; Perception; Sustainability; Users